Kualitas Pendidikan Keislaman Ponpes Nurul Islam Berbasis Sistem Informasi Manajemen - Ridlwan, H.M. Yusuf (Al-Riwayah : Jurnal Kependidikan, 2015)
The development of technology has influenced English teachers and students to improve their abilities in utilizing the technology in the teaching and learning process. Teachers have strong demand to utilize the information technology from the Internet as medium in the application of classroom teaching process. Because the use of technology has an important role as teaching and learning aid, Video cast is proposed to solve some problems encountered in the teaching of listening skill. The preliminary study conducted at building school, showed that the ability of the students in listening skills such as note taking, finding main ideas, finding detail information, and summarizing is still far from what was expected by the curriculum. To solve these problems, the researcher used Video cast as an instructional medium by implementing three steps in the teaching of listening, i.e. pre-listening, whilst-listening, and post-listening activities. This study utilized a collaborative action research design in which the researcher and the collaborative teacher worked together in designing the lesson plan, implementing the action, observing the action, and making reflection. The activities performed in the pre-listening step using Video cast were: giving explanation about the objective and assigned tasks, showing students the video screen, finding some important words, brainstorming on the topic learnt, setting the students into groups of five, and giving models of expression. In whilstlistening, the activities were: playing an English Video cast while doing note taking and discussing the main idea of the topic, playing again the Video cast while continuing the note taking activity and then discussing for finding detail information and summarizing, asking students’ opinion and then checking and discussing their answers. Post-listening activities were conducted by reviewing on the grammatical/structural rules and asking students’ feedback. As extensive listening, the follow-up activities were conducted by asking students to listen two new topics downloaded from the internet and then answering the worksheets about note taking, finding main ideas, finding detail information, and summarizing for each meeting.